If it's not what You are looking for type in the equation solver your own equation and let us solve it.
z in (-oo:+oo)
(3/4)*z+8 = (-1/4)*z // - (-1/4)*z
(3/4)*z-((-1/4)*z)+8 = 0
(3/4)*z+(1/4)*z+8 = 0
z+8 = 0 // - 8
z = -8
z = -8
| 6.3r-7=5.3r-7 | | 6n^2+25=-25 | | y^2+4y+5=4 | | -6(1-3v)=54 | | n+36=18 | | 2z-1/z-8 | | X/3+5=11 | | r+4=6 | | T=1/2*6+6 | | 0.0089x^2+1.1149+78.4491=300 | | p-44=-27 | | 2x^2-37x+174=0 | | (7-5)+11= | | 2x-4y=27 | | -2(7x-3x)=24 | | 3/4x=-1/2x^2+6 | | u/5+3=-5 | | x+(3/4)=4 | | 24-2=10 | | T=1/2c+6 | | 3x^2+8x-2=-7 | | 36x^2+134x+8= | | 5x+6y=9y-10 | | 3(x+2)+3(4-x)=-8 | | 2/x=x+4/x^2 | | 16=2c | | 2/3u-1=7/5u-7/5 | | 5y+10=12y+8 | | -4(3-12)= | | -3(5x-3x)=42 | | 198=82-u | | C=0.04t+6.9 |